2017
DOI: 10.1093/annonc/mdx049
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2, randomized, double-blind, placebo- controlled study of chemo-immunotherapy combination using motolimod with pegylated liposomal doxorubicin in recurrent or persistent ovarian cancer: a Gynecologic Oncology Group partners study

Abstract: BackgroundA phase 2, randomized, placebo-controlled trial was conducted in women with recurrent epithelial ovarian carcinoma to evaluate the efficacy and safety of motolimod—a Toll-like receptor 8 (TLR8) agonist that stimulates robust innate immune responses—combined with pegylated liposomal doxorubicin (PLD), a chemotherapeutic that induces immunogenic cell death.Patients and methodsWomen with ovarian, fallopian tube, or primary peritoneal carcinoma were randomized 1 : 1 to receive PLD in combination with bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 26 publications
(31 reference statements)
3
48
0
Order By: Relevance
“…However, consistent with literature reports, we have found motolimod has weak activity on TLR7 in addition to its agonistic activity over TLR8 indicating it is in fact 5 a TLR7/8 dual agonist though it predominantly targets TLR8 (35). Motolimod is administered subcutaneously, a systemic dosing route (36,37). However, the clinical doses used for motolimod were relatively low and its efficacy appeared to be limited suggesting motolimod had a narrow therapeutic index (36,37).…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, consistent with literature reports, we have found motolimod has weak activity on TLR7 in addition to its agonistic activity over TLR8 indicating it is in fact 5 a TLR7/8 dual agonist though it predominantly targets TLR8 (35). Motolimod is administered subcutaneously, a systemic dosing route (36,37). However, the clinical doses used for motolimod were relatively low and its efficacy appeared to be limited suggesting motolimod had a narrow therapeutic index (36,37).…”
Section: Introductionsupporting
confidence: 88%
“…Motolimod is administered subcutaneously, a systemic dosing route (36,37). However, the clinical doses used for motolimod were relatively low and its efficacy appeared to be limited suggesting motolimod had a narrow therapeutic index (36,37). Nevertheless, unlike other TLR7/8 dual agonists, motolimod can be dosed systemically suggesting its weaker activity on TLR7 relative to other TLR7/8 dual agonists might contribute to its improved tolerability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase II randomized double‐blind, placebo‐controlled trial was performed in patients with recurrent or persistent ovarian cancer. Although motolimod in combination with PLD did not improve clinical outcomes compared to placebo, the overall survival was significantly different between the two groups .…”
Section: Tlr8mentioning
confidence: 75%
“…In a Phase II randomized, double-blind trial, 297 subjects with recurrent epithelial ovarian carcinoma were treated with PLD (for inducing immunogenic tumor cell death) in combination with either VTX-2337 or placebo for 28-day cycles until disease progression. [164]. It was shown that PLD and VTX-2337 combination did not significantly improve the PFS [4.8 versus 5.2 months in the PLD plus placebo; log rank one-sided P=0.943, HR=1.21] and OS [18.1 versus 18.9 months in PLD plus placebo; log rank one-sided P=0.923, HR=1.22] of the treated subjects.…”
Section: Bdca-1+ and Bdca-3+ Blood Dcs And Targeting Them With Tlr8 mentioning
confidence: 99%